Energy efficiency maximization resource allocation algorithm in wireless-powered backscatter communication network - Yongjun XU; Bowen GU; Qianbin CHEN; Jinzhao LIN (Tongxin xuebao)
In order to alleviate the energy consumption problem caused by the increasing number of Internet of things (IoT) nodes,an energy-efficient (EE) maximization based resource allocation algorithm was proposed for multi-carrier wireless-powered backscatter communication network.Firstly,a multivariable and nonlinear resource allocation model was formulated to jointly optimize transmit power,transmission time,reflection coefficient,and energy-harvesting allocation coefficient,where the maximum transmit power constraint of the power station and the minimum harvested energy constraint at the backscatter device were considered.Then,the original non-convex optimization problem was transformed into a convex one which was solved by using Dinkelbach’s method and the variable substitution approach.Furthermore,the analytical solution of the resource allocation problem was obtained based on Lagrange dual theory.Simulation results verify that the proposed algorithm has better EE by comparing it with the existing algorithm under pure backscatter mode and algorithm under the harvested-then-transmit mode.